Human embryonic and induced pluripotent stem cells express TRAIL receptors and can be sensitized to TRAIL-induced apoptosis - Vinarsky, Vladimir; Krivanek, Jan; Rankel, Liina; Nahacka, Zuzana; Barta, Tomas; Jaros, Josef; Andera, Ladislav; Hampl, Ales (Stem cells and development, 2013)
Death ligands and their tumor necrosis factor receptor (TNFR) family receptors are the best-characterized and most efficient inducers of apoptotic signaling in somatic cells. In this study, we analyzed whether these prototypic activators of apoptosis are also expressed and able to be activated in human pluripotent stem cells. We examined human embryonic stem cells (hESC) and human-induced pluripotent stem cells (hiPSC) and found that both cell types express primarily TNF-related apoptosis-inducing ligand (TRAIL) receptors and TNFR1, but very low levels of Fas/CD95. We also found that although hESC and hiPSC contain all the proteins required for efficient induction and progression of extrinsic apoptotic signaling, they are resistant to TRAIL-induced apoptosis. However, both hESC and hiPSC can be sensitized to TRAIL-induced apoptosis by co-treatment with protein synthesis inhibitors such as the anti-leukemia drug homoharringtonine (HHT). HHT treatment led to suppression of cellular FLICE inhibitory protein (cFLIP) and Mcl-1 expression and, in combination with TRAIL, enhanced processing of caspase-8 and full activation of caspase-3. cFLIP likely represents an important regulatory node, as its shRNA-mediated down-regulation significantly sensitized hESC to TRAIL-induced apoptosis. Thus, we provide the first evidence that, irrespective of their origin, human pluripotent stem cells express canonical components of the extrinsic apoptotic system and on stress can activate death receptor-mediated apoptosis.
Keywords: Gene Expression Regulation; Caspase 3; TNF-Related Apoptosis-Inducing Ligand; Caspase 8; kaspasa 3; Cell Proliferation; homoharringtonin; Harringtonines; Myeloid Cell Leukemia Sequence 1 Protein; Pluripotent Stem Cells; protein TRAIL; signální transdukce; buněčná diferenciace; Protein Synthesis Inhibitors; Drug Synergism; Signal Transduction; pluripotentní kmenové buňky; FLIP (buněčný); RNA, Small Interfering; synergismus léků; embryonální kmenové buňky; inhibitory syntézy proteinů; CASP8 and FADD-Like Apoptosis Regulating Protein; Embryonic Stem Cells; harringtoniny; Receptors, TNF-Related Apoptosis-Inducing Ligand; lidé; Homoharringtonine; Humans; malá interferující RNA; regulace genové exprese; fas Receptor; receptory TNF - typ I; apoptóza; proliferace buněk; Receptors, Tumor Necrosis Factor, Type I; kaspasa 8; TRAIL receptory; antigeny CD95; Apoptosis; Cell Differentiation; protein MCL-1